Unity 2017 AI game programming : leverage the power of artificial intelligence to program smart entities for your games /: leverage the power of artificial intelligence to program smart entities for your games. (2018) - Barrera, Ray; Kyaw, Aung Sithu; Swe, Thet Naing
No abstract available